A novel index to evaluate resource allocation pattern in panicles in Japanese rice cultivars. (3rd April 2022) - Yabe, Shiori; Yoshida, Hiroe; Fushimi, Erina; Yamasaki, Masanori; Maeda, Hideo; Hayashi, Takeshi; Nakagawa, Hiroshi
ABSTRACT: The major impact of both genotypic and environmental factors on grain-filling efficiency of rice ( Oryza sativa L. ) makes evaluating cultivar's grain-filling characteristics highly complicated. To assess grain-filling characteristics, the allocation index ( Alli ) was defined as a novel indicator representing the pattern of resource allocation in panicles. Alli was calculated as the ratio of source of yield utilized for producing well-filled grains to the total source consumed in a panicle, using estimated grain weight distribution data. We measured the Alli of 91 Japanese rice cultivars grown under nine environments involving multiple years, cropping seasons, three sites, and flag leaf clipping. Each cultivar's stability in Alli was evaluated using the data of various sink–source balance conditions. As a result of integrated analysis of multiple cultivars, we observed a trade-off relationship between the stability of Alli and the stability of mean weight of well-filled grains ( mu2 ). The popular high-yielding cultivars Hokuriku 193 and Takanari showed high stability of Alli and mu2 under various sink–source balance conditions. Among the 91 cultivars, Hokuriku 193 showed stable characteristics with a high sink-filling ratio. Our results demonstrate that the grain weight distribution and Alli could be used as novel indicator of grain-filling characteristics, and that the trade-off relationship between the stability of Alli and mu2 should be considered when we select cultivars for multi-environmental cultivation. Abstract : uf0001